Adaptive setting of OLTC to improve power transfer capability of power systems - Abu-Siada, Ahmed; Islam, Syed; Masoum, Mohammed (Institute of Electrical and Electronic Engineers, 2008)
On load tap changing transformer (OLTC) has become a vital link in modern power systems. It acts to maintain the load bus voltage within its permissible limits despite any load changes. This paper discusses the effect of different static loads namely; constant power (CP), constant current (CI) and constant impedance (CZ) on the maximum power transfer limit from the generation to the load centre through the OLTC branch and in turn on the static stability margin of power systems. Then the paper introduces a novel approach for the on-line determination of the OLTC settings in order to improve the power transfer capability of transmission systems. The proposed approach is tested based on the simulation of a six-bus power system. Numerical results prove that the setting of transformer OLTC in terms of the load model has a major effect on the maximum power transfer in power systems. The adaptive settings of OLTC improve the power transfer capability according to the system operating condition.